High-precision estimate of g4 in the 2D Ising model - Caselle, M.; Hasenbusch, Martin; Pelissetto, Andrea; Vicari, Ettore (Journal of physics. A, Mathematical and general, 2000)
We compute the renormalized four-point coupling in the 2D Ising model using transfer-matrix techniques. We greatly reduce the systematic uncertainties which usually affect this type of calculation by using the exact knowledge of several terms in the scaling function of the free energy. Our final result is g4 = 14.697 35(3).
Im Titel ist die Zahl vier bei "g4" tiefgestellt
Gesehen am 08.07.2022